The Biodeversity of Mangrove in Ngantep Coastal, Malang District - Rona Aji Lestyaningrum; Mohammad Mahmudi; Nuddin Harahab (Graduate Program, 2017)
The purpose of this research are (1) to identify and analyze mangrove vegetation on the Ngantep Coast; (2) Identify associated biota in mangrove vegetation on the Coast Ngantep. The research was conducted in the Coast Ngantep area of Kabupaten Malang in april 2016. The method of measurement mangrove by using the method the combination and line transect plot with line plot 10 x 10 m2 long, in each line there are subplot with 5x5 m2 and 2x2 m2 long. The categories of sample will be discribed were trees, sapling and seedling. The result of thie researh found that the composition and the vegetation level of mangrove forest divided into IVI Sonneratia alba (tree) 128.63%, (sapling) 62.19%; Excoecaria agallocha (sapling) 63.72%; Xylocarpus granatum (sapling) 29.45%; Rhizophora mucronata (seedling) 116.21% and Nypa fruticans (seedling) 83.79%. The number of IVI discribe that Sonneratia alba very strong influence for the stability of ecosystem in mangrove forest in sute research. There were five families that make up the mangrove vegetation: Lythraceae, Rhizophoraceae, Euphorbiaceae, Meliaceae and Arecaceae. Mangrove vegetation on the Ngantep Coast dominated by the mangrove species of Sonneratia alba, with the low ecosystem show not yet stable. Fauna in mangrove vegetation Ngantep Coast become form between two groups of terrestrial and aquatic.Keywords: associated biota, biodiversity, composition, mangrove, structure